DAYA DUKUNG PANGAN DALAM MENDUKUNG KETERSEDIAAN PANGAN PROVINSI SUMATERA SELATAN - Sabrina Sabila (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2020)
South Sumatra Province has the potential of agricultural land, especially rice food, so it is necessary to manage agricultural land optimally to support the availability in meeting food needs. This research was focused on the carrying capacity of food that aimed to determine the carrying capacity of land/food based on supply and demand of land/food so that it can be known that the carrying capacity of regional food is sufficient or not in meeting food needs. This research method used a quantitative descriptive. The results showed the South Sumatra Province's food carrying capacity based on the incoming category/surplus category with a value of 3.32 or 2,167,003.04 tons of rice, but still included in the budget and deficit areas, would be adjusted to those that entered a large surplus. While the regions that indicated the lowest deficit level at the score limit of 0.93-1.89 were five regencies/cities, while the deficit at the score limit was 0.08-0.95 as many as four regencies/cities. Regions that are indicated deficit become the main priority to be supported by regions indicated by large surpluses.